Optimizing the Development of Space-Temporal Orientation in Physical Education and Sports Lessons for Students Aged 8-11 Years - Denisa-Mădălina Bălănean; Cristian Negrea; Eugen Bota; Simona Petracovschi; Bogdan Almăjan-Guță (MDPI AG, 2022)
The purpose of this research was to analyze how we can improve the space-temporal orientation ability with the help of physical exercises in physical education and sports lessons. In total,148 children between the ages of 8 and 11 participated in this study (M = 9.70; SD = 0.79). They were subjected to three tests, which measured general intelligence (Raven Progressive Matrices) and space-temporal orientation skills (Piaget-Head test and Bender-Santucci test). The tests were carried out both in the pre-test and in the post-test period. In the case of participants in the experimental group, a specific program was applied for a period of 12 weeks. The results showed that general intelligence level was identified as a predictor of spatial-temporal orientation (beta = 0.17, t = 2.08, p = 0.03) but only for the Piaget-Head test. Similarly, no differences between children's age groups were identified in any of the spatial-temporal orientation test scores. However, children in the "+9" age category had higher scores on the intelligence test compared to younger children (77.31 vs. 35.70). In conclusion, the intervention program had a positive effect on spatial orientation skills.